Making ereference works findable - Ramaswamy, Mohan; Baillargeon, Tara; Simser, Charlene N. (My University, 2008)
The Internet has significantly changed how libraries provide and library users access information. Libraries increasingly acquire electronic reference (eReference) books while collection of their print counterparts is diminishing. eReference books are not found on libraries' reference shelves and may easily go unnoticed. Libraries face the dilemma of how to make eReference books more accessible to patrons since they are buried in the catalog. K-State Libraries are addressing this challenge by utilizing enhanced metadata behind OPAC records to create browseable eReference lists. The lists are also published as RSS feeds which can be pushed to users. The article describes an approach that does not require programming skills and may be used by subject librarians and catalogers to make eReference books more accessible to patrons.
Keywords: Electronic reference works; eReference; Findability; Canned search; Canned query; Browsable finding aid; Ebook; OPAC